Bregmaceros anchovia sp. nov., a new codlet species from the western Pacific Ocean (Gadiformes: Bregmacerotidae) - Ho, Hsuan-Ching; Endo, Hiromitsu; Lee, Chia-Lien; Chu, Tah-Wei (Zootaxa, 2020)
A new codlet species is described from Japan, Taiwan, Indonesia and Australia. It is distinguished from its congeners by having a pointed snout extending beyond jaws, a stripe of black dots above anal-fin base, a black vertical band on caudal-fin base, and the following combination of characters: ventral surface of head and abdomen devoid of melanophores; ventral portion of abdominal vertebrae with a pointed parapophysis and a blunt ventral post-zygapophysis; peritoneum, pyloric caeca, and intestine pale; dorsal-fin rays 46–52; anal-fin rays 47–55; pectoral-fin rays 15–17; principal caudal-fin rays 12‒14; caudal vertebrae 35‒39; total vertebrae 50–54. Furthermore, as a result of this study, Bregmaceros pescadorus Shen described from southwestern Taiwan is herein recognized as a junior synonym of Bregmaceros nectabanus Whitley.